2017
DOI: 10.3892/mmr.2017.7663
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of coding gene mutations in mitochondrial DNA in esophageal cancer

Abstract: The aim of the present study was to detect mutations in the coding genes of mitochondrial DNA (mtDNA) in three esophageal cancer cell lines and in tumor tissues obtained from 30 patients with esophageal cancer, to investigate the relationship between protein‑ and RNA‑coding gene mutations and esophageal cancer. mtDNA was extracted and the coding genes were sequenced and analyzed by comparing the sequencing results with the complete mitochondrial genome of Homo sapiens. The results revealed 39 mutations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Reducing mTOR activity increases autophagic flux, reduces reactive oxygen species (ROS) and increases cellular replicative lifespan. Importantly, mTOR regulates mitochondrial function via different mechanisms, including the modulation of transcription and translation of important mitochondrial genes [46].…”
Section: The Progeria Cell and Energymentioning
confidence: 99%
“…Reducing mTOR activity increases autophagic flux, reduces reactive oxygen species (ROS) and increases cellular replicative lifespan. Importantly, mTOR regulates mitochondrial function via different mechanisms, including the modulation of transcription and translation of important mitochondrial genes [46].…”
Section: The Progeria Cell and Energymentioning
confidence: 99%
“…For example, Jiang et al (41) analyzed the nd1, nd4 and GaPdH levels in plasma and blood cells from 75 patients with thyroid cancer, which indicated that the ratio of nd1/nd4 in thyroid cancer was abnormally elevated. liu et al (42) found a total of 39 gene mutations in human esophageal cancer cells (EC9706, Te-1 and eca109). among them, the mutation frequency of the mitochondria encoded cytochrome B, nd5 and nd4 genes was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, MT- ND5 encodes a core subunit of Complex I, essential for electron transport from NADH to ubiquinone in the mitochondrial respiratory chain, so that variants in this gene and others related to this process may lead to impairment in OXPHOS and an increase of reactive oxygen species (ROS) generation, which can contribute to cancer proliferation and metastasis 36,37 . In fact, a high rate of mutations in MT-ND5 has been reported in esophageal cancer 38 .…”
Section: Discussionmentioning
confidence: 99%